Compendium : Coastal Management Practices in West Africa - Existing and Potential Solutions to Control Coastal Erosion, Prevent Flooding and Mitigate Damage to Society - World Bank (Washington, DC: World Bank, 2022)
Erosion and flooding are the most visible consequences of coastal zone degradation in West Africa. Man-made and natural processes, aggravated by the effects of climate change, cause erosion and flooding. These threatened densely populated coasts, the nerve center of the region’s demographic and economic growth. Every year, coastal degradation takes a heavy toll on human life and socio-economic prosperity. Moreover, the Intergovernmental Panel on Climate Change (IPCC) projections suggest that coastal erosion and flooding in West Africa is set to increase in the 21st century. Understanding the hazards and managing the coastline sustainably is a major challenge for the development of the region. The West Africa Coastal Areas Management Program (WACA) supports ongoing efforts led by countries and regional institutions to strengthen the resilience of communities and ecosystems. This is achieved by providing financing, facilitating access to knowledge and deepening dialogue around development challenges. The main objective of the Compendium: Coastal Management Practices in West Africa is to make knowledge on coastal management practices available to practitioners and decision-makers engaged in building coastal resilience in West Africa. At the same time, it informs any stakeholder concerned by risks related to coastal erosion and flooding. It complements technical catalogs on vulnerability to erosion, flood risks and flood protection infrastructure in West Africa.